Siderophore-mediated iron trafficking in humans is regulated by iron - Liu, Zhuoming; Mueller, Sebastian (Journal of molecular medicine, 2012)
Siderophores are best known as small iron binding molecules that facilitate microbial iron transport. In our previous study we identified a siderophore-like molecule in mammalian cells and found that its biogenesis is evolutionarily conserved. A member of the short chain dehydrogenase family of reductases, 3-hydroxy butyrate dehydrogenase (BDH2) catalyzes a rate-limiting step in the biogenesis of the mammalian siderophore. We have shown that depletion of the mammalian siderophore by inhibiting expression of bdh2 results in abnormal accumulation of cellular iron and mitochondrial iron deficiency. These observations suggest that the mammalian siderophore is a critical regulator of cellular iron homeostasis and facilitates mitochondrial iron import. By utilizing bioinformatics, we identified an iron-responsive element (IRE; a stem-loop structure that regulates genes expression post-transcriptionally upon binding to iron regulatory proteins or IRPs) in the 3′-untranslated region of the human BDH2 (hBDH2) gene. In cultured cells as well as in patient samples we now demonstrate that the IRE confers iron-dependent regulation on hBDH2 and binds IRPs in RNA electrophoretic mobility shift assays. In addition, we show that the hBDH2 IRE associates with IRPs in cells and that abrogation of IRPs by RNAi eliminates the iron-dependent regulation of hBDH2 mRNA. The key physiologic implication is that iron-mediated post-transcriptional regulation of hBDH2 controls mitochondrial iron homeostasis in human cells. These observations provide a new and an unanticipated mechanism by which iron regulates its intracellular trafficking.